The Association between Subclinical Hypothyroidism and Epicardial Adipose Tissue Thickness - Belen, Erdal; Degirmencioglu, Aleks; Zencirci, Ertugrul; Tipi, Fatih Fahri; Altun, Ozgur; Karakus, Gultekin; Helvaci, Aysen; Zencirci, Aycan Esen; Kalaycioglu, Ezgi (KOREAN SOC CARDIOLOGY, 2015)
Background and Objectives: Subclinical hypothyroidism (SH) is considered to be a potential risk factor for cardiovascular disease. Epicardial adipose tissue (EAT) thickness is also closely related to cardiovascular disorders. The aim of this study was to evaluate whether SH is associated with higher EAT thickness. Subjects and Methods: Fifty-one consecutive patients with SH and 51 healthy control subjects were prospectively enrolled into this trial. Thyroid hormone levels, lipid parameters, body mass index, waist and neck circumference, and EAT thickness measured by echocardiography were recorded in all subjects. Results: Mean EAT thickness was increased in the SH group compared to the control group (6.7 +/- 1.4 mm vs. 4.7 +/- 1.2 mm, p<0.001). EAT thickness was shown to be correlated with thyroid stimulating hormone level (r=0.303, p=0.002). Multivariate logistic regression analysis revealed that EAT thickness was independently associated with SH \{odds ratio (OR): 3.87, 95\% confidence interval (Cl): 1.92-7.78, p<0.001

OR: 3.80, 95\% Cl: 2.18-6.62, p<0.001\}. Conclusion: Epicardial adipose tissue thickness is increased in patients with SH compared to control subjects, and this increase in EAT thickness may be associated with the potential cardiovascular adverse effects of SH.
Keywords: Cardiovascular diseases; Echocardiography; Epicardium; Hypothyroidism; Visceral adipose tissue